2003
DOI: 10.1093/emboj/cdg135
|View full text |Cite
|
Sign up to set email alerts
|

GRIM-19, a death-regulatory gene product, suppresses Stat3 activity via functional interaction

Abstract: Signal transducer and activator of transcription 3 (Stat3) is a latent cytoplasmic transcription factor that can be activated by cytokines and growth factors. Stat3 plays important roles in cell growth, anti-apoptosis and cell transformation, and is constitutively active in various cancers. We examined its potential regulators by yeast two-hybrid screening. GRIM-19, a gene product related to interferon-beta- and retinoic acid-induced cancer cell death, was identified and demonstrated to interact with Stat3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
213
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(231 citation statements)
references
References 57 publications
13
213
5
Order By: Relevance
“…We have begun collecting more tumor tissues to address these questions. We and others have recently shown that GRIM-19 binds to STAT3 and inhibits its gene stimulating functions (Lufei et al, 2003;Zhang et al, 2003). In this regard, GRIM-19 appears to behave like the VHL protein, which binds to transcription factor HIF1 and prevents its gene stimulatory function (Iliopoulos et al, 1996;Maxwell et al, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…We have begun collecting more tumor tissues to address these questions. We and others have recently shown that GRIM-19 binds to STAT3 and inhibits its gene stimulating functions (Lufei et al, 2003;Zhang et al, 2003). In this regard, GRIM-19 appears to behave like the VHL protein, which binds to transcription factor HIF1 and prevents its gene stimulatory function (Iliopoulos et al, 1996;Maxwell et al, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…GRIM-19 was originally claimed as a nuclear protein, 10 but was later shown to be a mitochondrial protein. 11,12,14 In a recent review by Kalvakolanu, 34 it was proposed that GRIM-19 may initiate apoptosis, like cytochrome c and AIF, by translocation from the mitochondria to the nucleus upon IFN-b/RA stimulation. To test this hypothesis, we analyzed the cellular localization of GRIM-19, as well as other MRC subunit proteins, in the absence and presence of IFN-b/RA.…”
Section: Discussionmentioning
confidence: 99%
“…11 GRIM-19 was also identified as a negative regulator of signal transducer and activator of transcription (Stat)3. 12,13 To reveal its physiological role, we generated GRIM-19-deficient mice by gene targeting. 14 Although the deletion of GRIM-19 causes embryonic lethality, isolated GRIM-19 À/À blastocysts displayed abnormal mitochondrial structure and morphology.…”
mentioning
confidence: 99%
“…17 Furthermore, GRIM-19 has also been shown to repress the activity of the Signal Transducer and Activator of Transcription 3 (Stat3) and inhibit v-Src-induced oncogenic transformation and metastatic behavior of cells. 18,19 Thus, GRIM-19 is a good candidate gene to study the etiopathogenesis of mitochondrion-rich tumors.…”
Section: Introductionmentioning
confidence: 99%